Réponses

2014-09-16T18:42:03+02:00
1) 7 - 3 (4 - 2x)  - 5 (2 - 3 (x - 5))
= 7 - 12 - 6x - 5 (2 - 3x + 15)
= 7 - 12 - 6x - 10 + 15x - 75
= - 6x + 15x + 7 - 12 - 10 - 75
= 9x + 90

3) 3x - 2 - x = 13 - 2x
       9      6        2
18x - 12 - 9x = 351 - 54x
   54        54        54
18x - 12 - 9x = 351 - 54
9x = 351 - 54 + 12
9x = 309
x = 309/9
x = 103/3

4) x - 2 - 2x + 1 = 1 - x
     3          4          2
4x - 8 - 6x + 3 = 6 - 6x
   12        12         12
4x - 8 - 6x + 3 = 6 - 6x
4x + 6x - 6x = 6 + 8 - 3
4x = 11
x = 11/4
x = 2,75